2020
DOI: 10.1371/journal.pone.0228435
|View full text |Cite
|
Sign up to set email alerts
|

Adversity, social capital, and mental distress among mothers of small children: A cross-sectional study in three low and middle-income countries

Abstract: Background Maternal mental health is becoming recognized as a global health priority. Mental distress among mothers of young children may be exacerbated by exposure to adversity. Social capital may buffer the impact of adversity on mental distress during the postnatal period and beyond. This paper examines the relationship between adversity, cognitive social capital and mental distress among mothers of young children in three low and middle-income countries. Methods This study uses data from the Young Lives st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Among women who have young children, previous research in Ethiopia, India, and Vietnam found that women who experience family-related stressful life events, such as illness or death within the household and financial uncertainty, are more likely to experience episodes of severe mental distress. 7 With the ongoing need to social distance, family and community networks may struggle and pregnant and postpartum women may feel even more vulnerable and isolated over a lack of social support.…”
mentioning
confidence: 99%
“…Among women who have young children, previous research in Ethiopia, India, and Vietnam found that women who experience family-related stressful life events, such as illness or death within the household and financial uncertainty, are more likely to experience episodes of severe mental distress. 7 With the ongoing need to social distance, family and community networks may struggle and pregnant and postpartum women may feel even more vulnerable and isolated over a lack of social support.…”
mentioning
confidence: 99%
“…In another study, researchers looked at Ethiopia, India and Vietnam and examined the relationship between adversity, cognitive, social capital and mental distress among mothers with children aged between 6 and 18 months postpartum and found that types of adversity experienced varied by country. 13 The results from India and Vietnam showed that having an additional older woman member in the household was a protective factor for the MMH of participants; however, there was no significant evidence of the same effect for the Ethiopian sample. 13 This suggests that understanding the context is essential to develop culturally sensitive care models.…”
Section: Introductionmentioning
confidence: 94%
“… 13 The results from India and Vietnam showed that having an additional older woman member in the household was a protective factor for the MMH of participants; however, there was no significant evidence of the same effect for the Ethiopian sample. 13 This suggests that understanding the context is essential to develop culturally sensitive care models. However, an observational method adopted by Gausman et al 13 may not guarantee causation, and the participants were requested to report significant life events that they believed to be important, which suggests that cultural and social norms could influence how they interpret the severity of the events.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations